2007
DOI: 10.1111/j.1365-2788.2006.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding distress in people with severe communication difficulties: developing and assessing the Disability Distress Assessment Tool (DisDAT)

Abstract: There was no evidence that pain has any specific signs or behaviours. The preliminary and assessment phases showed that distress was a useful clinical construct in providing care. The DisDAT reflected patients' distress communication identified by a range of carers, and provided carers with evidence for their intuitive observations of distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 58 publications
(38 reference statements)
4
101
0
1
Order By: Relevance
“…Similarly, other potentially suitable schemes (e.g. The Disability Distress Assessment Tool :DisDAT [6], and some vocal affect expression assessment tools [7]) all neglected the important interactions between expression and impression (response), an important issue highlighted in both the intellectual disability literature [8] and the emotion research literature [9]. Despite a small sample size (n=13), Wright et al [2] found that the VR-CoDES could reliably code (with satisfactory inter-and intra-coder scores) dental patients' expressions of emotional distress, as well as dental professionals' responses to patients' cues and concerns.…”
Section: Verona Coding Definitions Of Emotional Sequences (Vr-codes) mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other potentially suitable schemes (e.g. The Disability Distress Assessment Tool :DisDAT [6], and some vocal affect expression assessment tools [7]) all neglected the important interactions between expression and impression (response), an important issue highlighted in both the intellectual disability literature [8] and the emotion research literature [9]. Despite a small sample size (n=13), Wright et al [2] found that the VR-CoDES could reliably code (with satisfactory inter-and intra-coder scores) dental patients' expressions of emotional distress, as well as dental professionals' responses to patients' cues and concerns.…”
Section: Verona Coding Definitions Of Emotional Sequences (Vr-codes) mentioning
confidence: 99%
“…It was also possible that researchers and dental workers unfamiliar with that individual are disadvantaged in identifying and responding to emotional cues compared to carers who have greater knowledge and familiarity with those individuals as indicated in Regnard et al's study [6]. Unlike the DisDAT [6], no baseline behaviour in a non-clinical setting was obtained in the VR-CoDES to help detect behavioural changes as indicators for emotional distress. This lack of an additional video recording of the patient in the company of another adult (e.g.…”
Section: Patient's Expression Of Emotional Distressmentioning
confidence: 99%
“…for those with Down's syndrome or Fragile X syndrome (Hoghton, 2010). If the person is unable to communicate pain, an assessment tool, such as the Disability Distress Assessment Tool (DisDAT), should be used (Regnard et al, 2006). …”
Section: Nhs Health Checkmentioning
confidence: 99%
“…Assessing pain in patients with Alzheimer's dementia appears to be even more complex again (Regnard et al, 2006). Specialist palliative care services must also recognize that the assessment instruments used for the general population for both pain and nutrition needs are rarely helpful for people with intellectual disability (McCallion & McCarron, 2004;.…”
Section: Knowledge and Skills Of Addressing Nutrition Hydration And mentioning
confidence: 99%